2018
DOI: 10.1039/c7ra12735a
|View full text |Cite
|
Sign up to set email alerts
|

A feasible strategy for self-assembly of gold nanoparticlesviadithiol-PEG for photothermal therapy of cancers

Abstract: We designed and explored self-assembled gold nanoparticles (SAGNPs) by introducing dithiol modified polyethylene glycol (PEG) for internanoparticle cross-linking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…According to statistical analysis, calculated T according to Equation 1 at different time points of 0, 3, 5, 7, and 10 min showed significant time and dose dependent differences in comparison with the control samples (P < 0.001). Both AuNP@Ng/Cur and AuNP samples, respectively, exhibited 5.1 and 8.4 • C temperature raise compared with control (Figure 3E; Fu et al, 2018). The thermal images show the temperature change of samples after 10 min of exposure of NIR radiation for two different concentration of AuNP, nanogel, and AuNP@Ng/Cur (Figure 3D).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to statistical analysis, calculated T according to Equation 1 at different time points of 0, 3, 5, 7, and 10 min showed significant time and dose dependent differences in comparison with the control samples (P < 0.001). Both AuNP@Ng/Cur and AuNP samples, respectively, exhibited 5.1 and 8.4 • C temperature raise compared with control (Figure 3E; Fu et al, 2018). The thermal images show the temperature change of samples after 10 min of exposure of NIR radiation for two different concentration of AuNP, nanogel, and AuNP@Ng/Cur (Figure 3D).…”
Section: Resultsmentioning
confidence: 92%
“…The thermal analysis of synthesized AuNP@Ng/Cur, AuNP, and control (nanogel) were characterized by measuring the temperature at different time points of 0, 3, 5, 7, and 10 at two different concentrations of 2.5 and 5 μg/ml under NIR exposure(Fu et al, 2018 ). Using thermal camera GUIDE B from Sensmart, the thermal image and measured temperature were obtained and the temperature change (ΔT) was determined using the following equation (Fu et al, 2018 ):…”
Section: Methodsmentioning
confidence: 99%
“…The therapeutic ratio, in this case, is related to the maximum radiation dose by which the death of cancer cells is locally controlled and the minimum radiation dose by which cells in healthy tissues have low acute and late morbidity [38–40]. Properties such as biocompatibility, chemical stability, inertness, relatively low cytotoxicity, thermal efficacy, and ease of detection make gold an eligible candidate to enhance PPT [41,42]. Moreover, the novel approaches for synthesis [5,43], as well as the application of GNPs as biomarkers and contrast agents (CAs) [44–46], and the progress in combinatorial cancer therapy pave the ways toward the theranostic use of GNPs in addition to PTT [6,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…1 ). The use of PEG(SH) 2 8000 as a reducing agent indicated that some of the thiol groups were oxidized and formed sulfonic acid (SO 3 H) derivatives as well as crosslinks of the polymer chains by disulfide bonds [ 47 , 52 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%